The Concept of Bio-regions in Advanced Ecology - Nowak, Maria E. (Studia Ecologiae et Bioethicae, 2006)
The article analyses the notion of the environment, showing the concept of bio-regions and presenting the main principles of advanced Ecology. In addition, it explores bio-regions in the light of advanced Biology.